Where are the children? Exploring the boundaries between text and context in the study of place and space in four different countries. (31st May 2013) - Haldar, Marit; Rueda, Eréndira; Wærdahl, Randi; Mitchell, Claudia; Geldenhuys, Johanna
<x xml:space="preserve">Abstract</x> In this article, we demonstrate how the cultural conceptions of a team of five researchers from different cultural and national backgrounds can be used as a source of knowledge during a collective, self‐reflexive analytical process. While collectively analysing texts describing daily life produced by first‐grade children and their parents in China, Norway, South Africa and the United States, the research team engaged in a collectively negotiated analytical process, which we refer to as an 'analytic negotiating method'. The strength of this process rests on the ability to examine critically the boundaries between the researcher's contextual conceptions and conceptions derived from the texts. Engaging in this kind of negotiated analytical process contributes to scholarship by working towards a level of self‐reflexivity that makes the link between empirical data and researcher interpretation more transparent and produces a sensitivity to context that allows insights into the conceptions of childhood that operate cross‐culturally.